1991
DOI: 10.1037/0033-2909.110.2.215
|View full text |Cite
|
Sign up to set email alerts
|

Empirical status of cognitive theory of depression.

Abstract: Studies testing cognitive theory of depression (Beck, 1963, 1987) and defining depression as a clinical syndrome are reviewed. Many aspects of the theory's descriptive claims about depressive thinking have been substantiated empirically, including (a) increased negativity of cognitions about the self, (b) increased hopelessness, (c) specificity of themes of loss to depressive syndromes rather than psychopathology in general, and (d) mood-congruent recall. Evidence that depressive thinking is especially inaccur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
295
3
14

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(338 citation statements)
references
References 220 publications
26
295
3
14
Order By: Relevance
“…This claim has been supported by empirical studies that examined the association between cognitive errors and depressed mood (e.g. Deal and Williams, 1988;Haaga et al, 1991). CEQ scores also positively correlated with the PDI-21 scores.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This claim has been supported by empirical studies that examined the association between cognitive errors and depressed mood (e.g. Deal and Williams, 1988;Haaga et al, 1991). CEQ scores also positively correlated with the PDI-21 scores.…”
Section: Discussionmentioning
confidence: 68%
“…You think to yourself, "I couldn't learn skiing, so I doubt if I can learn to play tennis." This bias is associated with depression (Deal and Williams, 1988;Haaga et al, 1991). Surprisingly, no previous studies have assessed whether this tendency is more frequent in people with delusions or with delusional ideation.…”
Section: Introductionmentioning
confidence: 99%
“…In reviewing the empirical status of these hypotheses, Haaga et al (1991) found substantial support for them by past research. Specifically, those who have more dysfunctional cognitions are more likely to be unhappy or depressed than those who have fewer such cognitions (Crandell & Chambless, 1986;Dobson & Shaw, 1986).…”
Section: Relevant Theory and Past Research Cognitive Theory Of Depresmentioning
confidence: 98%
“…Similarly, the automaticity of cognitive processes has been upheld (Bargh & Tota, 1988;Wenzlaff, Wegner, & Roper, 1988). Haaga et al (1991) review a large number of studies supporting another assumption, that dysfunctional cognitions lead to depression or unhappiness.…”
Section: Relevant Theory and Past Research Cognitive Theory Of Depresmentioning
confidence: 99%
“…In Beck's cognitive model of depression, negative beliefs about the self, the world, and the future are at the core of depression, whereas the reformulated learned helplessness theory emphasizes the importance of a pessimistic attributional style, defined as interpreting negative events as internal, stable, and global. Numerous studies have shown that depressed individuals are characterized by increased dysfunctional attitudes (Haaga et al, 1991), whereas relatively fewer studies have investigated the impact of positive biases such as increased optimism about the future (Taylor and Brown, 1988) on mood and dysfunctional cognitions.…”
Section: Introductionmentioning
confidence: 99%